Persuasion and apate in Gorgias - SPANGENBERG, PILAR (2010)
In Gorgias’ mind there are tensions regarding the relations of persuasion, dóxa and deceit that rest on the fact that some of the oppositions he admits turn on strong axiology while his art of rhetorical defense undermines such distinctions. To explain these tensions we propose a dual origin of his thought: Gorgias, as inheritor of treatises from both the poetic and the Parmenidean traditions, postulates a schema that lies between the aesthetic and the philosophical.